Cryopreservation in liquid nitrogen of Brazilian orchid seeds Miltonia flavescens Lindl. - Baudraz de Paula, Jean Carlo (2020)
Miltonia flavescens is a species vulnerable to extinction, which justifies research on preservation methods. Cryopreservation in liquid nitrogen (LN) consists of maintaining biological material at a low-temperature (-196 °C). Thus, the aim of the experiment is to evaluate the influence of different cryoprotective solutions on cryopreservation in LN of the Brazilian orchid Miltonia flavescens seeds. The experiment was conducted in a completely randomized design (CRD), with eight treatments and six replications. The treatments were composed as follows: control; immersion in LN, no cryoprotectant adding; and immersion in LN, with the addition of cryoprotectants: sucrose 0,4 mol L-1; glycerol 2 mol L-1; protection by vitrification in solution (PVS)1; PVS2; PVS2 + 1% phloroglucinol, and PVS3. Except for the control treatment, which was kept in a freezer (10±2 °C), the others remained frozen for 15 days. After this period, the viability of the seeds was evaluated. These seeds were sown and, 30 days after germination, then the frequency of protocorm formation was verified. Before the cryopreservation, the seeds showed 75% viability and 9.5% water content. After cryopreservation, the seeds varied between 67 to 75% viability. However, treatment with glycerol 2 mol L-1 exhibited lower performance than the others (58%). The control treatment showed a higher percentage of protocorm formation (71%) followed by treatments PVS1 (63%), PVS2 (64%), and PVS2PHLO (66%). For the purpose of preserving Miltonia flavescens seeds in liquid nitrogen for a prolonged period, the treatments PVS1, PVS2, and PVS2PHLO proved to be viable and promising alternatives.